Safety and Efficacy of Trans-Ulnar Coronary Intervention - Islam, AHM Waliul; Bhuiyan, Azfar H; Munwar, Shams; Islam, Nighat; Siddique, Atique Bin; Yousuf, Intekhab; Ahmed, Tamzeed; Talukder, Sahabuddin; Reza, AQM; Alam, MS (Cardiovascular Journal, 2018)
Background: Primary aim of our study to evaluate the safety and feasibility of percutaneous Trans- Ulnar approach for coronary angiogram and intervention. Methods: Patient whom radial pulse was very feeble and difficult to cannulate and having very good volume Ulnar pulse were selected in this study. Total 48(Male 37: Female 11) patients were enrolled in this very preliminary study who underwent elective coronary angiogram (CAG) and subsequent adhoc percutaneous coronary intervention (PCI) in same sitting. Total 11 stents were deployed in 10 territories. Mean ages of male and female were 59 and 52 years respectively. Associated coronary artery artery disease (CAD) risk factors were dyslipidemia, high blood pressure, diabetes mellitus, positive family history of CAD and smoking (all male). Results: Among the study group; 36(75%) were Dyslipidemic, 35(73%) were hypertensive; 34(70.1%) patients were Diabetic, FH 11(23%), and 12(25%) were all male smoker.PCI performed in 9 patients i.e., 18.8% of the total population of this study. Angiographic diagnosis of TVD 8(16.6%), DVD 6(25%), SVD 17 (35.4%), Normal Coronaries 8(16.6%), ISR or patent stent 5(10.4%), Severe Calcified disease 4(12%). Common stented territory was LAD 6(66%), LCX 2(22%) and RCA 2 (22%). Vaso-spasm was not noted as it is quite often in trans-radial approach. Procedural complication like hematoma was not present. Conclusion: We conclude that trans-ulnar approach is a safe, feasible and effective alternative to Transfemoral and Trans-radial approach, specially due to sluggish flow or feeble radial pulsation with severe spasm of radial artery for coronary angiogram and subsequent PCI. Cardiovasc. j. 2018; 11(1): 5-9